Eco-friendly Board from Oil Palm Frond and Citric Acid - Firda Aulya Syamani; Sasa Sofyan Munawar (Masyarakat Peneliti Kayu Indonesia, 2013)
The utilization of oil palm fronds as composite board raw material has developed due to the declining wood supply. Currently, citric acid is used as natural adhesive on the wood-based moldings to reduce the use formaldehyde-based resin. Citric acid has carboxylic acid functional group that can react with hydroxyl functional group from cellulose by esterification reaction. This paper explain the production of board from oil palm frond and citric acid, then elaborate their physical and mechanical properties. Oil palm fronds were processed with ring flaker to produce particles with 1 5 cm length. The particles were dried until the moisture content reached 6%. Citric acid solution was obtained by stirring 700 g citric acid in 1000 ml water. Citric acid solution were sprayed onto particles. The weight of citric acid were 10%, 15% and 20% based on oil palm fronds’ dry weight. Boards were produced with density target of 0.6 g/cm3 and pressure at 1N/mm2 for 10 min. The hot pressing temperatures were varied at 140ºC, 160ºC, 180ºC, and 200ºC. Physical and mechanical test were performed according to JIS A 5908-2003. The MOR, MOE, IB and SW values of boards with 15 wt% citric acid content and pressed at 200oC were 5.85 N/mm2, 1067.03 N/mm2, 0.26 N/mm2 and 88.80 N respectively. The optimum condition for board production obtained upon citric acid content and pressing temperature in a range of 15% 20% and 180ºC 200ºC, respectively.